Discussing the Reform of Physical Education Instruction Based on the Basic Skills Competition for Physical Education Majors in Chongqing Municipality's General Colleges and Universities - guangxin cheng; Zhongchen Zhang; Zhiming Shi (Journal of Education, Health and Sport)
Purpose:In order to provide theoretical support for the basic skills competition of college and university students, the reform of physical education instruction in colleges and universities, and the talent development system for physical education majors, we analyze and research the basic skills competition in order to identify the issues that currently exist and propose solutions.